The influence of culture on impulse buying - Cakanlar, Aylin; Nguyen, Tram (The Journal of consumer marketing, 2019)
Purpose This study aims to expand the understanding of impulse buying behavior by looking further into the role of culture in cross-cultural contexts. Design/methodology/approach A cross-cultural questionnaire was administered across three countries, namely, Sweden, Turkey and Vietnam. Findings Culture impacts impulse buying behavior of subjects with different cultural backgrounds. However, the findings also indicate that other factors may affect impulse buying behavior. Originality/value The cultural role on impulse buying was brought up by a few researchers in the literature, but Hofstede’s model of four cultural dimensions and their relationship to impulse buying behavior is tested for the first time in the literature across three different countries: Sweden, Turkey and Vietnam, which, respectively, represent northern Europe, southern Europe/a part of West Asia and South East Asia.